Information and communication technologies for the socialization of children and adolescents with deaf and hearing disabilities: an integrative review (Research, Society and Development, 2021)
The inability to acquire oral language harms the deaf individual, as it significantly interferes in relations with the world and reduces symbolic exchanges with the social environment. Some technological tools can help, expanding and favoring communication between these people. The aim of this study is to investigate the influence of Information and Communication Technologies on the socialization process of deaf and hearing impaired children and adolescents. It is an integrative literature review, carried out between the months of September 2020 and January 2021, whose searches were carried out in the MEDLINE, LILACS, Web Of Science databases using the descriptors: Child; Adolescent; Hearing Impaired People; Information Technology; Socialization. After applying the filters and refinements of titles and abstracts, the final result was 11 articles that made up the corpus of analysis of this study. Two categories of analysis emerged from the analysis of the studies: “assistive technologies”, among which stand out software applications, auditory and audiovisual technologies; and the contribution of technologies to socialization, which highlighted Information and Communication Technologies (ICTs) as important tools for the socialization of children and adolescents, especially in the school environment. The use of technological tools constitutes a strategy for the social participation of children and adolescents in various contexts, be they in television and social media, family and school, public resources, and also in the health sector. The research showed positive social impacts resulting from the implementation of ICTs to foster the socialization of deaf and hearing impaired children and adolescents.